Gadobutrol-Enhanced Magnetic Resonance Imaging of the Breast in the Preoperative Setting: Results of 2 Prospective International Multicenter Phase III Studies. Issue 7 (July 2016) - Sardanelli, Francesco; Newstead, Gillian M.; Putz, Barbara; Jirakova Trnkova, Zuzana; Trimboli, Rubina M.; Abe, Hiroyuki; Haverstock, Daniel; Rosenberg, Martin
Abstract : Objectives: The aim of this study was to evaluate the diagnostic efficacy of gadobutrol enhanced preoperative breast magnetic resonance imaging (MRI) in 2 prospective studies. Materials and Methods: Approval of ethics committees and informed consent from patients were obtained. Both Gadobutrol-Enhanced MR Mammography (GEMMA) trials followed a standardized protocol using 1.5 T scanners. After unenhanced scans, patients received 0.1 mmol/kg of gadobutrol for the dynamic study. Six independent blinded readers, 3 for GEMMA1 and 3 for GEMMA2, assessed unenhanced images and, 2 or more weeks apart, contrast-enhanced plus unenhanced breast MRI images (CE-BMRI), using a standard 5-region scheme. Another 6 independent readers (3 for each study) evaluated mammograms alone. Sensitivity was calculated taking into account the identification of regions harboring malignancies (within-patient sensitivity), whereas specificity was based on cancer-free breasts. The first patient from each center was used for site qualification and blinded reader training and excluded from the efficacy analyses. Reference standard was pathology for regions harboring malignancy and a combination of negative pathology, mammography, and ultrasound for cancer-free regions. Results: Of 906 breast cancer patients enrolled in 13 countries in the 2 studies, 865 received gadobutrol and 787 were evaluated for diagnostic performance (390 in GEMMA1 and 397 in GEMMA2). Within-patient sensitivity, that is, the detection rate of malignant disease extent per patient, ranged from 80% to 89% for CE-BMRI and was significantly superior to unenhanced breast MRI alone (37%–73%) and to mammography alone (68%–73%) for all readers in both trials. Specifity of the CE-BMRI ranged from 83% to 95%. Conclusion: In a very large multicenter preoperative setting, gadobutrol-enhanced breast MRI demonstrated high levels of sensitivity and specificity, consistent with published data on breast MRI. Abstract : Supplemental digital content is available in the text.